A Review on an Optimized path finding on Road Network using ant colony Algorithm - Rakshak, Gitali; Pimpalkar, Amit (International Journal of Computer Sciences and Engineering, 2014)
The large usage of smart phones and GPS enabled devices, which provides location based services, the necessity of outsourcing spatial data has grown rapidly over the past some years. Nevertheless a challenging problem remains in the database outsourcing paradigm is that the authentication of the query results at the client side. In this data owner delegates management of its database to the third party instant of directly served the request of clients. Ensuring spatial query integrity is critical because third party service provider is not always trustworthy. We propose an efficient road network optimized path finding technique using ant colony algorithm which utilizes the network Voronoi diagram and neighbors to prove the integrity of query results. Unlike previous work that consider only one data owner party but we are considering multi data owner party. This experiment will run on Google Android mobile devices.